Using probiotics to improve nutrient digestibility and gut-health of weaned pigs: a comparison of maternal and nursery supplementation strategies - Galli, Gabriela Miotto; Andretta, Ines; Levesque, Crystal; Stefanello, Thais; Carvalho, Camila Lopes; Perez Pelencia, Jorge Yair; Bueno Martins, Gabriel; Souza de Lima Cony, Bruna; Romeiro de Oliveira, Caroline; Franceschi, Carolina Haubert; Kipper, Marcos (Frontiers in Veterinary Science, 2024)
Maternal probiotic supplementation has been found to have a positive impact on the gut health of piglets, not only during the lactation period, but also after weaning. Providing probiotics to nursery pigs is also a common strategy for supplementation. However, there is limited data available that compares the effectiveness of these strategies. The goal of this study was to evaluate which would be the most effective strategy to improve nutrient digestibility, energy metabolism, and intestinal health in weaned pigs considering the maternal or nursery options. A total of 32 newly weaned pigs were randomly split into a 2 × 2 factorial arrangement considering maternal probiotic supplementation (with or without) in gestation-lactation and probiotic supplementation in the nursery period (with or without). After weaning, experimental diets were provided for 22 days. Total fecal and urine collection was performed from day 15 to 21. Blood samples were collected from all pigs on days 3 and 22 of the experiment to assess serum biochemistry and intestinal permeability. All pigs were euthanized on day 22 for intestinal tissue collection. Pigs born from probiotic-fed sows had greater (P<0.05) total tract digestibility of dry matter (+1%) and gross energy (+1.3%), and greater (P<0.05) metabolizable energy coefficient (+1.3%), which resulted in a 46 kcal/kg increase (P<0.05) in the metabolizable energy content of the diet. Nitrogen intake (P=0.035), uptake (P=0.007), and retention (P=0.012) were all increased in these pigs. Fecal moisture was reduced in pigs born from probiotic-fed sows and pigs fed the probiotic diet only in the nursery (P<0.05). Pigs born from probiotic-fed sows had reduced intestinal permeability by 16% (P<0.05), whereas pigs fed the probiotic diet in the nursery only tended to improve this response (P<0.10). The villus:crypt ratio of pigs born from probiotic-fed sows was greater compared to the control (P<0.05), while serum levels of alanine aminotransferase were lower (P<0.05) compared to the control. Pigs born from probiotic-fed sows had increased nutrient digestibility and improved gut health. Therefore, it is concluded that supplementing the sow diets